A new species of Tenuipalpus Donnadieu (Acari: Tenuipalpidae) from Cedrela odorata L. (Meliaceae), from Bahia, Brazil, with ontogeny of chaetotaxy - Souza, Kaélem S.; Castro, Elizeu B. [UNESP]; Tassi, Aline D.; Navia, Denise; Oliveira, Anibal R. (Systematic and Applied Acarology Society, 2019)
A new species of Tenuipalpus Donnadieu (Acari: Tenuipalpidae), Tenuipalpus odoratus Souza, Castro & Oliveira sp. nov., is described from females, males, deutonymphs, protonymphs and larvae collected on Cedrela odorata L. (Meliaceae) from Ilhéus, Bahia, Brazil. A proposed ontogeny of leg chaetotaxy is also included.
Keywords: false spider mites; Neotropical; sensu lato group; taxonomy; Tetranychoidea